Vitamin K - Fairweather-Tait, Susan (Henry Stewart Talks, 2026)
Functions in the body, Dietary sources of vitamin K, Absorption, Metabolism, Biomarkers of intake and status, Deficiency, Excess, Dietary reference values for vitamin K for adults